Potential interactions among myricetin and dietary flavonols through the inhibition of human UDP-glucuronosyltransferase in vitro. (1st April 2022) - Li, Xichuan; Wang, Ce; Chen, Jinqian; Hu, Xia; Zhang, Hao; Li, Zhiying; Lan, Bei; Zhang, Wei; Su, Yanjun; Zhang, Chunze
Highlights: Myricetin exhibit potential food-drug interactions through the inhibition of hUGTs. Myricetin had strong inhibitory effects against UGT1A1, 1A3, 1A6, 1A7 and 1A10. Morin, kaempferol, quercetin and galangin also exhibit potential FDI towards hUGTs. Abstract: Myricetin is a dietary flavonol and possesses multiple bioactivities, which making it an excellent nutritional supplement and a new drug candidate. However, whether myricetin and other homologous dietary flavonols affect the activities of UDP-glucuronosyltransferases (UGT) enzymes and facilitated food-drug interactions remains unclear. Our results demonstrated that myricetin displayed broad-spectrum inhibition against human UGTs. Myricetin exhibited strong inhibitory effects against UGT1A1, 1A3, 1A6, 1A7, 1A10 (IC50 < 10 μM) with non-competitive inhibition type, while serving as a moderate inhibitor against UGT1A9 and 2B7 (IC50 range from 25 to 29 μM) with competitive and mixed inhibition type, respectively. In Silico docking was carried out to explore the binding models and free energies of myricetin towards inhibitory UGTs. The potential risks of food–drug interactions after myricetin consumption were predicted by combining the in vitro inhibitory data and physiological data. The quantitative prediction in vivo of inhibition on gastrointestinal UGTs by myricetin showed that the inhibition against UGT1A1, 1A3, 1A6, 1A7, 1A9, 1A10 and 2B7 would likely occur with high risk. The follow-up findings demonstrated that morin, kaempferol, quercetin and galangin, the four homologous dietary flavonols, shared similar inhibition patterns towards UGTs. These findings altogether demonstrate that myricetin and homologous dietary flavonols have potent and broad-spectrum inhibitory effects against most human UGTs, thus suggest that much caution should be exercised when flavonols-rich foods or supplements are co-administered with UGT substrate drugs.